Leadership Styles and Emotional Intelligence of Women Entrepreneurs - Vijayakumar, Nivetha (Ushus Journal of Business Management, 2022)
As women entrepreneurs, women must be aware of their emotions and feelings since Emotional Intelligence(EI) is a key component of effective leadership. Leaders with high emotional intelligence are happier and are more committed to their organization (Abraham, 2000), and they also use positive emotions to visualize the improvements in the organization’s functions (George, 2000). The study focuses on the factors of EI and leadership that influence women entrepreneurs in their entrepreneurial activities, which also impact the success of the business. The quantitative approach will be followed throughout the study to measure the variables. The descriptive study is also employed to identify characteristics of women entrepreneurs who deal with managing leadership and emotional intelligence problems. The TEIQue (Trait Emotional Intelligence Questionaire) was used to measure EI, and Vannsimpco Leadership Survey (VLS) was used to determine the leadership styles. The study was conducted among 132 women entrepreneurs from South India. The findings of the study revealed that there is a significant relationship between EI and leadership. The educational level of entrepreneurs impacts both EI and leadership.